Re-Thinking Kebijakan Pembangunan dalam Perspektif Ekonomi Lokal: Studi Kasus Tambang Emas Batu Gosok – Labuan Bajo – NTT - Doddy Setiawan; Robert T. Herman (Binus Business Review, 2011)
This paper is a practical-theoretical study towards economic development policy. Unrealistic policy and planning approach, government management close and uncooperative system which considered intervening political interest rather than economic development are as one cause of stagnating economic development in several areas. Economic development that has been established by central government has not able to give velocity acceleration solution in economic development; it is the authority and power divergence that affecting local economic development. Economic policy through mining investment as one strategy development has been approved by district government and investors had affected long polemic. It needs further thought and study related to the policy so it could get the expected result and local economic development. This paper is purposed to give contributed thought of re-thinking policy economic development especially about gold mining investment decision in conservation area of Batu Gosok-Labuan Bajo-NTT.